Mechanisms participating in oxidative damage of isolated rat hepatocytes - Cervinková, Zuzana; Kriváková, Pavla; Lábajová, Anna; Rousar, Tomás; Lotková, Halka; Kucera, Otto; Endlicher, René; Cervinka, Miroslav; Drahota, Zdenek (Archives of toxicology, 2009)
The aim of the study was to evaluate time course and dose dependence of peroxidative damage induced by tert-butyl hydroperoxide (tBHP) in rat hepatocytes cultured in suspension and in monolayer. At the lowest (0.1 mM) concentration, decrease of cytosolic glutathione and discharge of mitochondrial membrane potential (MMP) could be detected. Significant increases in leakage of lactate dehydrogenase and in malondialdehyde concentrations together with decrease of pyruvate-dependent respiration were detected at higher tBHP concentrations (above 0.5 mM) and after longer periods of incubation. Changes in plasma membrane integrity were observed at 1 mM concentration of tBHP. Succinate-dependent oxidation was most resistant to peroxidative damages. Opening of the mitochondrial permeability transition pore was responsible for the discharge of mitochondria membrane potential. In the presence of cyclosporine A and succinate, the membrane potential could be restored. Our data showed that the most sensitive indicators of the peroxidative damage are changes of cytosolic glutathione concentration and MMP.
Keywords: Cell Survival; Oxidative Stress; oxidační stres; Malondialdehyde; Oxygen Consumption; cytosol; Mitochondria, Liver; Dose-Response Relationship, Drug; peroxidace lipidů; tert-Butylhydroperoxide; krysa rodu Rattus; Membrane Potential, Mitochondrial; oxidancia; zvířata; Cells, Cultured; Lipid Peroxidation; Cytosol; potkani Wistar; Glutathione; jaterní mitochondrie; L-Lactate Dehydrogenase; Rats, Wistar; Male; kultivované buňky; spotřeba kyslíku; terc-butylhydroperoxid; glutathion; Oxidants; Rats; Hepatocytes; vztah mezi dávkou a účinkem léčiva; Animals; mužské pohlaví; L-laktátdehydrogenasa; hepatocyty; membránový potenciál mitochondrií; malondialdehyd; viabilita buněk